1993
DOI: 10.1212/wnl.43.12.2534
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous glucose after out‐of‐hospital cardiopulmonary arrest

Abstract: Current practices of using limited amounts of glucose-containing solutions after cardiopulmonary arrest do not need to be changed. Blood glucose level on admission is a prognostic indicator but depends on the type of arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(24 citation statements)
references
References 0 publications
0
19
0
5
Order By: Relevance
“…Most human and animal studies of fluid infusion during CPR did not have a control group, [332][333][334][335][336][337][338][339][340][341][342][343] and 2 animal studies showed that normothermic fluid infusion during CPR caused a decrease in CPP. 344 -346 In addition to normothermic fluid, hypertonic and chilled fluids have been studied in animal and small human studies without a survival benefit.…”
Section: Fluidsmentioning
confidence: 99%
“…Most human and animal studies of fluid infusion during CPR did not have a control group, [332][333][334][335][336][337][338][339][340][341][342][343] and 2 animal studies showed that normothermic fluid infusion during CPR caused a decrease in CPP. 344 -346 In addition to normothermic fluid, hypertonic and chilled fluids have been studied in animal and small human studies without a survival benefit.…”
Section: Fluidsmentioning
confidence: 99%
“…In global cerebral isch emia, as seen in cardiac arrest survivors, elevated admission blood glucose levels are a prognostic indi cator, but seem to be more the sequel of prolonged CPR than the cause of adverse neurological outcome (Longstreth and Inui, 1984;Longstreth et al 1986Longstreth et al , 1993. In a study by Longstreth et al (1993), patients with out-of-hospital cardiac arrest were randomized to receive either 5% dextrose in water or half normal saline intravenously after the event. Overall, there was no difference in outcome between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…10,[65][66][67][68][69][70] Animal studies suggest that elevated postischemic blood glucose concentrations exacerbate ischemic brain injury, 71,72 and this effect can be mitigated by intravenous insulin therapy. 73,74 Seizures in the post-cardiac arrest period are associated with worse prognosis and are likely to be caused by, as well as exacerbate, post-cardiac arrest brain injury.…”
Section: Post-cardiac Arrest Brain Injurymentioning
confidence: 99%